PENDAMPINGAN GAPOKTAN MITRA ARJUNA MENUJU MASYARAKAT SADAR WISATA - Syasya Mas'udi; Eko Rizqi Purwowidodo; Ali Roziqin (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The community service that we are doing this time is tourism awareness. This dedication to the Mitra Arjuna Gapoktan in Tulungrejo Village, Bumiaji District, Batu City aims to assist the Gapoktan in terms of the tourism potential of the region. With the implementation of this community service, it is hoped that Gapoktan Mitra Arjuna will be more optimal in utilizing its natural potential. In order to create a tourism-aware community in this village, we are doing a number of things such as providing tourist facilities, assisting in the creation of promotional content, and outreach to awareness of nature's potential. Keywords: assistance, tourism awareness community, community service